DINAMIKA EKONOMI POLITIK GLOBAL DAN PEMBAGIAN KERJA INTERNASIONAL - Arwanto, Arwanto; Anggraini, Wike (Jurnal Politik Pemerintahan Dharma Praja, 2021)
This study aims to find out some dynamics and perspectives of the global political economy by using the literature review method. Economic nationalists place the state as the main actor. Meanwhile, economic liberals argue that the state should collaborate with other actors in the system. There are dynamics that shape the global political economy, which are international trade and transnational production. These two dynamics have implications for the global division of labor. International trade with the concept of 'comparative advantage' affects the specialization of the workforce. Meanwhile, transnational production with transnational corporations has implications for encouraging the division of labor around the world. However, there is skepticism about these dynamics. For example, they are believed to play a role in wage inequality, especially between a less skilled workforce and a more skilled workforce in the developing countries.